2019
DOI: 10.1051/epjam/2019004
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of acoustic metasurface in China

Abstract: Acoustic metasurface (AMS) is an important branch of metamaterials which has important applications in various fields such as earthquake protection, noise reduction, acoustic hiding, architectural acoustics, particle manipulation, and medical ultrasound and therapy. The AMS with subwavelength thickness can manipulate the acoustic wave by controlling the wavefront phase based on the generalized acoustic Snell's law. In this review, the research and application progresses of AMS in China were introduced, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Plane wave focusing with a discrete temperature gradient is a method combining an acoustic metasurface [31] with discrete temperature. The length of the metasurface was set to 1 cm, the frequency was set to 20 kHz, and the speed of sound was set to 343 m/s, yielding a wavelength of approximately 2 cm, thus meeting the design requirement of the metasurface.…”
Section: Modeling and Boundary Condition Settingmentioning
confidence: 99%
“…Plane wave focusing with a discrete temperature gradient is a method combining an acoustic metasurface [31] with discrete temperature. The length of the metasurface was set to 1 cm, the frequency was set to 20 kHz, and the speed of sound was set to 343 m/s, yielding a wavelength of approximately 2 cm, thus meeting the design requirement of the metasurface.…”
Section: Modeling and Boundary Condition Settingmentioning
confidence: 99%
“…The ingredient in Xinmailong injection is extracted from an American cockroach, in traditional Chinese medicine, it is a worm category, with the effects of dispersing stagnation and eliminating stagnation, detoxifying, and diuretic. Modern pharmacological studies have shown that small-molecule bioactive peptides in American cockroaches have effects on enhancing myocardial contraction and inhibiting myocardial remodeling [ 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elastic waves are a classical form of motion in engineering structures, and the mechanical vibrations of major equipment such as aerospace vehicles, underwater probes, and high-speed trains are essentially the superimposed effects of their internal elastic waves. With the depth of research, the regulation of elastic waves has gradually become the focus of attention, and the emergence of metasurface structures [1][2][3] in recent years is one of the means to effectively regulate elastic waves.…”
Section: Introductionmentioning
confidence: 99%